The effect of EVA and REVA's financial performance on shareholder value creation in the healthcare industry during the COVID-19 pandemic - Sanga, Marianus Hendrilensio; Yopie Kefi, Darwin; Sanam, Yefta (Institute of Computer Science (IOCS), 2024)
This study investigates the effect of value-added profitability metrics, specifically Economic Value Added (EVA) and Refined Economic Value Added (REVA), on shareholder value creation proxy by Market Value Added (MVA) in the Indonesia’s healthcare industry before and during the COVID-19 pandemic. We employed ordinary least squares (OLS) panel data regression model, with variable dummy to accommodate the COVID-19 pandemic. It uses a sample size of 14 companies, including 4 healthcare service sector companies and 11 pharmaceutical sector companies. The result: 1) EVA and REVA have significant influence in explaining the shareholder value creation of the healthcare industry in Indonesia before and during the pandemic. EVA had a positive effect on MVA in two periods, while REVA is negatif during the pandemic. 2) EVA and REVA metrics are superior in explaining shareholder value creation over traditional accounting metrics (ROCE, ROE and EPS). The implications: for academics, the calculation of EVA and REVA must be done properly and correctly, especially in calculating the cost of capital in order to provide accurate results. While, for practisioners, the consistency of value-added metrics shows the urgency of its application in evaluating financial performance and shareholder value creation in Indonesia and specifically the healthcare industry